Semi-quantitative Dust Hazard Analysis: Identification of the Ignition Sources and Quantification of the Probability - Leonardo Michele Carluccio; Aurora Lafiosca; Sara Perelli (Chemical Engineering Transactions)
Dust Hazard Analysis (DHA) is a risk assessment technique used for identifying, managing, and mitigating the risks related to the handling, production, and storage of combustible dusts. In a previous study, the efficacy of the use of a semi-quantitative approach (i.e., leveraging a Risk Matrix to assess the risk level associated with combustible dust, through the definition of severity and likelihood levels) has been analysed. This study is intended to deepen some aspects of the methodology, exploring, in particular, the approaches used to identify the probability of ignition during a semi-quantitative DHA. The identification of all the possible ignition sources and the consequent definition of a probability for each of these to be effective (i.e., to be able to ignite a cloud of dust, properly mixed with air inside explosibility limits) is a fundamental step to conduct a semi-quantitative DHA; for this reason, the aim of the present study is to discuss the possible scenarios related to the different ignition sources that could be present in a working environment where combustible dust is handled (e.g., electrical equipment, electrostatic discharge, etc., as described in the standard EN 1127-1), together with the approach used to determine the proper ignition probability to be used in the assessment. The study underscores the importance of the identification of all the possible ignition sources and the suggested approaches for the determination of the ignition probability within the framework of semi-quantitative DHA, where a Risk Matrix is used to evaluate the risk levels associated with identified dust-related scenarios.